Интеллектуальный анализ данных для систем промышленной автоматизации на основе искусственных иммунных систем - Самигулина, Г. А.; Самигулина, З. И. (НТУ "ХПИ", 2013)
Разработана технология сбора данных с реальных объектов промышленной автоматизации с использованием оборудования Schneider Electric и организации информационного обмена с интеллектуальной системой прогнозирования и управления на основе биологического подхода искусственных иммунных систем

The technology of data gathering from real objects of industrial automation with use of Schneider Electric equipment and the organization of an information exchange with the intellectual system of forecasting and control on the basis of the biological approach of the artificial immune networks is developed
The intellectual data analysis for industrial automation systems on the basis of artificial immune systems
Keywords: интеллектуальная система; оборудование Schneider Electric; молекула; организм; моделирование; оценка погрешностей; intellectual system; artificial immune systems; data analysis; systems of industrial automation; Schneider Electric equipment